Backtesting in VaR Models of Bitcoins - Shen, Jiadi (2018)
Bitcoins is the most famous cryptocurrency in the world and is getting more and more important as an investment product. But from bitcoins’ historical performance, it can be read that this cryptocurrency has large volatilities which brought many risks to investors. The purpose of this dissertation is trying to use Value at Risk(VaR) as the risk management tool for bitcoins. And Basic Historical Simulation, Hull White and Parametric methods are used in this dissertation to evaluate VaR of bitcoins.